2006
DOI: 10.2310/6650.2006.05013
|View full text |Cite
|
Sign up to set email alerts
|

Supportive Programs Increase Medical Students’ Research Interest and Productivity

Abstract: Although it is too early to assess the long-term effects, the research programs offered led to greater numbers of students who did research, including those in traditionally underrepresented groups. Moreover, students were highly satisfied with their experiences, with 80% feeling that it increased their interest in applying principles they learned to the practice of medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
95
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 21 publications
4
95
0
6
Order By: Relevance
“…5 Previous studies have already shown that medical students in the first years, who are studying basic sciences, are more eager to participate in clinical trials than students carrying out medical rotations. 8 Payment is also an important motivational factor for research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Previous studies have already shown that medical students in the first years, who are studying basic sciences, are more eager to participate in clinical trials than students carrying out medical rotations. 8 Payment is also an important motivational factor for research.…”
Section: Discussionmentioning
confidence: 99%
“…5 Preliminary studies demonstrate high levels of interest in research among medical students, with the intention of integrating scientific activity with their curricular activity. However, many of them do not understand the benefits of research during their training period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible way to address this problem is by setting time aside as part of the medical degree purely for research or creating opportunities for students outside term time such as summer elective programmes (Kemph et al 1984). Other suggestions have included starting research interest groups within medical schools as a way to coordinate student and supervisor involvement (Zier et al 2006). Such interest groups may also relieve some of the time pressure by encouraging medical students to share the workload amongst them and increase efficiency as a consequence.…”
Section: Challenges and Solutions To Medical Student Researchmentioning
confidence: 99%
“…On the contrary 89% students are unaware about the publication research and would not consider it as a good carrier option. 20 Students acquired the searching skills and 90% students were using PubMed,Google and Wikipedia as a search engines for their EviGenCHIP.…”
Section: Discussionmentioning
confidence: 99%